Service quality framework for mobile government services in Kingdom of Bahrain / Abdulla Jaafar Mohamed Hasan Ali - Abdulla Jaafar Mohamed , Hasan Ali (2022)
Service quality is the success of any organizations. The advancement of technology encourages the services providers to use electronic forms as new channels to deliver services for the public. Popularity of using smart devices by most of people, leads the government authority to use smart devices as a portal to deliver government services, which is called Mobile Government. The mGovernment authority face difficulties at measuring the service quality at the services delivered through smart devices, that leads the government service provider to use other service quality measurement scales to be used at the context of mGovernment portal. It is difficult to use other measurement scales at the environment of mGovernment services, because each of online service portal has its own features and criteria. The issue here is; there is a lack of integrated, compatible, and comprehensive service quality framework that can be used by government authorities to measure the service quality at mGovernment portal. Therefore, the study targeted the service category of (Government To Citizens – G2C) through the main research objectives of: a) To investigate the service quality dimensions of mGovernment services, b) To develop a service quality framework of mGovernment services, and c) To validate the service quality framework of mGovernment services. Using the Mixed-Method Approach, the researcher applied the Exploratory Sequential Design to integrate both qualitative and quantitative data to investigate the most appropriate factors for mGovernment Service Quality Framework. For qualitative method, interviews with experts were conducted to evaluate the proposed mGovernment quality dimensions with related constructs. While for quantitative method, online questionnaire survey was distributed at the Kingdom of Bahrain and a total valid sample of (934) were collected. Factor analysis were conducted using both Exploratory Factor Analysis (E.F.A.) and Confirmatory Factor Analysis (C.F.A.). The E.F.A. serves at the present study for correlations between variables, factor extraction, factor rotation, and to measure the reliability of the factors. The factor structure of mGovernment framework was verified using C.F.A. The final results show that the mGovernment Service Quality Framework consists of four main dimensions that are “a) Efficiency and Usability, b) Interaction, c) Information and Service Availability, and d) Privacy and Security” with a total of (28) quality constructs. The researcher recommends to conduct advanced analysis for each of the individual quality constructs related to mGovernment service quality.